Clinical and molecular analysis of 26 individuals with Noonan syndrome in a reference institution in Colombia. Issue 4 (10th December 2020) - Lores, Juliana; Prada, Carlos E.; Ramírez‐Montaño, Diana; Nastasi‐Catanese, José A.; Pachajoa, Harry
Abstract: Our aim was to characterize the phenotype and genotype of individuals with Noonan syndrome in Colombia. There are published cohorts of Noonan individuals from several countries in Latin America including Brazil, Chile, and Argentina, but none from Colombia. We described 26 individuals with NS from a single large referral center in the South West of Colombia using an established database in the genetics department and hospital records search using ICD‐10 codes. All patients included in this study were evaluated by a medical geneticist and have molecular confirmation of NS diagnosis. The median age at referral was 3.5 years (range, 0–39), and at molecular diagnosis was 5 years (range, 0–40). Patients mostly originated from the southwest region of Colombia (19/26, 73%). Pathogenic variants in PTPN11 are the most common cause of NS in Colombian individuals followed by SHOC2 and SOS1 variants. The prevalence of cardiomyopathy was low in this population compared to other populations. Further research is needed with a larger sample size and including different regions of Colombia to correlate our findings. This study provides new information about time to diagnosis of NS in Colombia, genotypes, and provides important information to help develop guidelines for diagnosis and management of this disease in the region.